Development of a conceptual framework for teaching-learning of spiritual care in nursing education - Ntombizodwa S.B. Linda; Hester C. Klopper; Deliwe R. Phetlhu (AOSIS, 2024)
Background: Conceptual frameworks are not only necessary for maintaining and preserving nursing knowledge through their unique contribution, but they also assist in the organisation and provision of complex nursing interventions. The lack of formal integration of spiritual care in health professions' education is blamed on the unavailability of guiding models among other challenges such as unavailability of relevant theories. Objectives: The objective of this article was to describe the process followed to develop a conceptual framework as the basis for a practice theory for teaching-learning of spiritual care in nursing. Method: An overall theory generative methodology was used. To develop the conceptual framework, conclusion statements deduced from empirical data using deductive and inductive strategies were applied. Results: The main concepts were identified, described, and classified. The relationship between concepts promoted synergy of the developed conceptual framework for teaching spiritual care in nursing. Conclusion: The developed conceptual framework was founded on the notion that knowledge from different sources can provide a solid base in theory generation. Therefore, the concepts of the developed conceptual framework were not only related to what is 'ideal'; instead, their significance was underpinned by the created universal meanings for effective purposeful communication. Therefore, sources used to obtain data were critical in the development of the conceptual framework because they constituted different ways of perceiving and understanding the world. Contribution: The conceptual framework does not only guide nursing interventions but framework also provides a philosophical guide in meeting patient-centred diverse needs.